PDE3A mutations cause autosomal dominant hypertension with brachydactyly - Maass, Philipp G.; Aydin, Atakan; Luft, Friedrich C.; Schaechterle, Carolin; Weise, Anja; Stricker, Sigmar; Lindschau, Carsten; Vaegler, Martin; Qadri, Fatimunnisa; Toka, Hakan R.; Schulz, Herbert; Krawitz, Peter M.; et al. (Nature Genetics, 2015)
Cardiovascular disease is the most common cause of death worldwide, and hypertension is the major risk factor. Mendelian hypertension elucidates mechanisms of blood pressure regulation. Here we report six missense mutations in PDE3A (encoding phosphodiesterase 3A) in six unrelated families with mendelian hypertension and brachydactyly type E (HTNB). The syndrome features brachydactyly type E (BDE), severe salt-independent but age-dependent hypertension, an increased fibroblast growth rate, neurovascular contact at the rostral-ventrolateral medulla, altered baroreflex blood pressure regulation and death from stroke before age 50 years when untreated. In vitro analyses of mesenchymal stem cell-derived vascular smooth muscle cells (VSMCs) and chondrocytes provided insights into molecular pathogenesis. The mutations increased protein kinase A-mediated PDE3A phosphorylation and resulted in gain of function, with increased cAMP-hydrolytic activity and enhanced cell proliferation. Levels of phosphorylated VASP were diminished, and PTHrP levels were dysregulated. We suggest that the identified PDE3A mutations cause the syndrome. VSMC-expressed PDE3A deserves scrutiny as a therapeutic target for the treatment of hypertension.
EVALuna2:25114